Performance Optimization of Piled Raft Foundations in Layered Soil under Uniform Vertical Loading Using Plaxis 3D - Biya Degefu Teji; Argaw Asha Ashango (Advances in Materials Science and Engineering)
Piled raft foundations are composite foundations that combine piles and raft to support civil engineering structure and to reduce the settlement. The data were obtained from Addis Ababa, Ethiopia. In this study, the effects of raft thickness, number of piles, pile length, spacing of piles, and pile diameter on the response of piled-raft foundations were investigated using the finite element-based program Plaxis 3D for layered soils (medium to very stiff high plastic silty clay and medium to very dense silty sand soil) subjected to uniform vertical loading. The results showed that increasing the thickness of the raft from 0.7 m to 1.7 m reduced the differential settlement by 78.21% when there were 16 piles. However, the maximum settlement also increased by 2.81%. Increasing the number of piles from 4 to 16 reduced the maximum settlement by 22.09% for a pile spacing of 4D. Moreover, increasing the pile length from 9 m to 15 m contributed to a 19.49% reduction in the total settlement for a pile spacing of 5D. Therefore, the current study provides a useful framework for analyzing and designing large piled-raft foundations.